2012
DOI: 10.1021/ef201500r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Nitrogen Compounds in Hydrotreated and Untreated Shale Oil by Electrospray Ionization (ESI) Fourier Transform Ion Cyclotron Resonance Mass Spectrometry (FT-ICR MS)

Abstract: Shale oil has attracted more attention, as a very important substitutable fuel resource. In the present research, the classes and structures of nitrogen species in hydrotreated and untreated Fushun shale oil (FSO) are characterized by electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). Experimental results have demonstrated that most of the nitrogen compounds in FSO are removed effectively during the hydrotreatment. N1 and N2 classes are dominant in FSO, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 35 publications
4
97
0
Order By: Relevance
“…Among the basic nitrogen compounds N 1 , N 2 , N 1 O 1 , and N 1 O 2 identified by the positive-ion mass spectra from VGOs, the N 1 class species were the most abundant, and N 1 O 1 class species took the second place, which is similar to the results reported by other authors. 4,5,14 While N 1 O 2 class was not found from VGO cut-2, and N 2 class was only identified from VGO cut-4, indicating the complexity of the basic nitrogen compounds increased with the increasing of boiling point of subfractions. In dewaxed VGOs, the N 1 class was also the predominant one, and followed by N 1 O 1 class.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Among the basic nitrogen compounds N 1 , N 2 , N 1 O 1 , and N 1 O 2 identified by the positive-ion mass spectra from VGOs, the N 1 class species were the most abundant, and N 1 O 1 class species took the second place, which is similar to the results reported by other authors. 4,5,14 While N 1 O 2 class was not found from VGO cut-2, and N 2 class was only identified from VGO cut-4, indicating the complexity of the basic nitrogen compounds increased with the increasing of boiling point of subfractions. In dewaxed VGOs, the N 1 class was also the predominant one, and followed by N 1 O 1 class.…”
Section: Resultsmentioning
confidence: 94%
“…Wu et al 16 pointed out that the quantitative determination to all species identified is not currently The N 1 O 1 class species are likely be comprised of a pyridine ring and a furan ring or a double bond of carbon and oxygen. 5 While N 1 O 2 class species may be suggested more complex structures: a pyridine ring and two furan rings, or a pyridine ring, a furan ring and a double bond of carbon and oxygen, etc. And the N 2 class species are likely amphoteric molecules including two heterocyclic rings: a pyridine ring and a pyrrole ring, 5 were enriched in the heavy fraction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations